(untitled) (FAN, TA’LIM, TEXNOLOGIYA VA ISHLAB CHIQARISH INTEGRATSIYASI ASOSIDA RIVOJLANISH ISTIQBOLLARI, 2024)
This article explores the concept of phoneme alteration, a fundamental process in linguistic evolution. It provides an overview of how phonemes, the smallest sound units in language, change over time, leading to significant linguistic transformations. Key types of phoneme alterations—such as assimilation, dissimilation, elision, insertion, metathesis, and neutralization— are discussed with illustrative examples.